Hamstrings are most susceptible to injury during the early stance phase of sprinting - Orchard, J. W. (British Journal of Sports Medicine, 2012)
The first publications which considered the time of onset in the gait cycle for hamstring strains concluded that early stance was the highest risk period. The rationale proposed was that external joint moments were much higher in stance phases than swing because of the presence of high hip and knee joint reaction forces secondary to the ground reaction force (GRF). Ralph Mann's original argument has been rejected by many subsequent authors, perhaps because of the dogma that muscles probably strain during eccentric contractions. This is a widely held belief despite experimental muscle strains being able to be produced during concentric (shortening) contractions.